Konsumsi sagu keluarga berdasarkan preferensi dan persepsi nilai sosial sagu keluarga di Kabupaten Konawe Provinsi Sulawesi Tenggara - Imanuddin Imanuddin; Abidillah Mursyid; Joko Susilo (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2008)
Background: Variety of staple foods has an important role in supporting food security of the community. However, more people who used to consume non rice turn to consume rice nowadays. Sago (sinonggi) as one of staple foods is consumed less every year in Sulawesi Tenggara. This may be due to some factors, among others are preferences of the community to sago, perception of the community about social value of sago and sago availability.Objective: To identify the consumption of sago of the family in relation to preferences and perception of the family about social value of sago, availability of sago in the family level and its distribution.Method: The study was observational with cross sectional design. Research location was determined using cluster stratified random sampling technique. Three sub districts represented category of far, medium, and close from district capital. Two villages represented category of close and far from sub district capital. Distribution of 196 households samples were taken with proportionate sampling technique in 6 chosen villages. Variables of the study consisted of preferences to sago, perception about social value of sago, sago consumption and availability of sago in the household. Data were obtained through structured interview using questionnaire and observation. Bivariable analysis used chi-square; whereas multivariable used logistic regression.Results: Sago as complementary food of rice was consumed everyday by 65% of households. Preference level of sago was like (70.4%) and favorite (29.6%). Household perceived social value of sago as low (74.0%) and not low (26.0%). Sago was always available throughout the years at distribution level.Conclusions: There were differences in the consumption of sago based on the family preferences of sago, the family perception of sago social values, and the household availability of sago. Sago availability in the household was the most dominant factor of sago consumption in the household.